Orofacial pain : a guide to medications and management - Clark, Glenn T.; Dionne, Raymond (Chichester [England] : Wiley-Blackwell, 2012)
"Pain is a preoccupation in dentistry, but the dentist's role has expanded beyond the treatment of dental pain to being one of the most involved in the treatment of orofacial pain. Orofacial Pain: A Guide to Medications and Management guides readers through the rational use of medications for the treatment of chronic orofacial pain, including oral, injectable and topical medications. It also provides relevant information about treatment choices for managing neuropathic and musculoskeletal pain, headache and uncommon orofacial pain disorders"--Provided by publisher.
Interventional therapy and injected agents for orofacial pain and spasm (including botulinum toxin) / Glenn T. Clark, Alan Stiles -- Treatment for oral mucositis and non-infectious, non-neoplastic oral ulcerations / Satish Kumar, Antonia Teruel, Glenn T. Clark -- Management of orofacial pain and other co-morbidities in oropharyngeal and nasopharyngeal cancer patients / Saravanan Ram, Glenn T. Clark -- Burning mouth syndrome : an update on diagnosis and treatment methods / Piedad Suarez Durall, Glenn T. Clark -- Headaches with a focus on chronic daily HA medications / Soma Sahai-Srivastava, Glenn Clark -- Differential diagnosis and management of masticatory myogenous pain and dysfunction / Glenn T. Clark -- Diagnosing and managing chronic trigeminal neuropathy / Glenn T. Clark -- Temporomandibular joint arthritis : implications, diagnosis, and management / Antonia Teruel, Jack S. Broussard Jr., Glenn T. Clark -- Five oral motor disorders : habitual tooth clenching and other involuntary oral motor disorders / Glenn T. Clark, Saravanan Ram -- Diagnosis and treatment of TMJ internal derangements / Glenn T. Clark.
Includes bibliographical references and index.
Keywords: Orofacial pain -- Treatment; Facial pain -- Treatment; MEDICAL -- Surgery -- General; Facial Pain -- drug therapy; Facial Pain -- therapy; Electronic books